Elevated basophil count is associated with increased risk of endometriosis - Feng, Q; Shigesi, N; Guan, J; Rahmioglu, N; Bafadhel, M; Paddon, K; Hubbard, C; Zondervan, K; Becker, C; Hellner, K (Bioscientifica, 2024)
Immunological dysregulation plays a fundamental role in the inflammatory aspects of endometriosis. Circulating blood leukocytes, one of the most abundant immune cell populations in the human body, have been shown diagnostic significance in some diseases. Nevertheless, the association between peripheral blood leukocyte counts and endometriosis remains unexplored to date. We analyzed two targeted study cohorts: a tertiary center cohort (Endometriosis at Oxford University (ENDOX) Study: 325 cases/177 controls) and a large-scale population study (UK Biobank (UKBB): 1537 cases/6331 controls). In both datasets, peripheral venous blood sample results were retrieved, and counts of leukocyte subpopulations, including neutrophils, lymphocytes, monocytes, eosinophils, and basophils, were analyzed. Logistic regression models were used to investigate the association of leukocyte subtype alterations with endometriosis status, adjusting for confounding factors. We demonstrate that a higher blood basophil level is associated with increased odds of endometriosis. This association was first discovered in the ENDOX cohort (basophils >0.04 × 109/L: OR 1.65 (95% CI: 1.06–2.57), Ptrend = 0.025) and replicated in the UKBB dataset (basophils >0.04 × 109/L: OR 1.26 (95% CI: 1.09–1.45), Ptrend = 0.001). Notably, women with basophil counts in the upper tercile had significantly increased odds of having stage III/IV endometriosis (ENDOX study: OR = 2.30, 95% CI (1.25–4.22), Ptrend = 0.007; UKBB study (OR = 1.40, 95% CI (1.07–1.85), Ptrend = 0.015). None of the other leukocyte subtypes showed an association. Our findings suggest an association between inflammatory responses and the pathogenesis of endometriosis; future studies are warranted to investigate whether the association is causal.